2-Year BMI Changes of Children Referred for Multidisciplinary Weight Management - Jennifer K. Cheng; Xiaozhong Wen; Kristen D. Coletti; Joanne E. Cox; Elsie M. Taveras (International Journal of Pediatrics)
Objective. To examine body mass index (BMI) changes among pediatric multidisciplinary weight management participants and nonparticipants. Design. In this retrospective database analysis, we used multivariable mixed effect models to compare 2-year BMI z-score trajectories among 583 eligible overweight or obese children referred to the One Step Ahead program at the Boston Children’s Primary Care Center between 2003 and 2009. Results. Of the referred children, 338 (58%) attended the program; 245 (42%) did not participate and were instead followed by their primary care providers within the group practice. The mean BMI z-score of program participants decreased modestly over a 2-year period and was lower than that of nonparticipants. The group-level difference in the rate of change in BMI z-score between participants and nonparticipants was statistically significant for 0–6 months (P=0.001) and 19–24 months (P=0.008); it was marginally significant for 13–18 months (P=0.051) after referral. Younger participants (<5 years) had better outcomes across all time periods examined. Conclusion. Children attending a multidisciplinary program experienced greater BMI z-score reductions compared with usual primary care in a real world practice; younger participants had significantly better outcomes. Future research should consider early intervention and cost-effectiveness analyses.